Introduction to pharmaceutical biotechnology. - Bhatia, Saurabh; Naved, Tanveer; Sardana, Satish (IOP (Series). Release 6., 2019)
Introduction to Pharmaceutical Biotechnology, Volume 3: Animal tissue culture and biopharmaceuticals offers background information and knowledge on all aspects of this fascinating subject, including stem cell treatment, in vitro organ systems and cell culture technology. This book and the previous two volumes are a must read for undergraduate and postgraduate pharmacy and biotechnology based students, research scholars and academicians.